Rearrangements in the 5′ Nontranslated Region and Phylogenetic Analyses of Cucumber Mosaic Virus RNA 3 Indicate Radial Evolution of Three Subgroups - Roossinck, Marilyn J. (American Society for Microbiology, 1999)
Cucumber mosaic virus (CMV) has been divided into two subgroups based on serological data, peptide mapping of the coat protein, nucleic acid hybridization, and nucleotide sequence similarity. Analyses of a number of recently isolated strains suggest a further division of the subgroup I strains. Alignment of the 5′ nontranslated regions of RNA 3 for 26 strains of CMV suggests the division of CMV into subgroups IA, IB, and II and suggests that rearrangements, deletions, and insertions in this region may have been the precursors of the subsequent radiation of each subgroup. Phylogeny analyses of CMV using the coat protein open reading frame of 53 strains strongly support the further division of subgroup I into IA and IB. In addition, strains within each subgroup radiate from a single point of origin, indicating that they have evolved from a single common ancestor for each subgroup.